Η μεσοπολεμική πεζογραφία. Τόμος 8ος : από τον πρώτο ως τον δεύτερο παγκόσμιο πόλεμο 1914-1939 (Σοκόλης, 1996)
Γιάννης Σκαρίμπας -- Κώστας Σούκας -- Τατιάνα Σταύρου -- Γιάννης Γ. Σφακιανάκης -- Αγγελος Τερζάκης -- Παύλος Φλώρος -- Πέτρος Χάρης